Effect of Orally Administered Atractylodes macrocephala Koidz Water Extract on Macrophage and T Cell Inflammatory Response in Mice. (7th August 2018) - Kwak, Tae-Kyung; Jang, Hyung-Seok; Lee, Mi-Gi; Jung, Young-Sung; Kim, Dae-Ok; Kim, Yoon-Bum; Kim, Jong-In; Kang, Hee
Abstract : The rhizome of Atractylodes macrocephala Koidz (AM) is a constituent of various Qi booster compound prescriptions. We evaluated inflammatory responses in macrophages and T cells isolated from mice following oral administration of AM water extract (AME). Peritoneal exudate cells were isolated from thioglycollate-injected mice and alterations in scavenger receptors were examined. Peritoneal macrophages were stimulated with lipopolysaccharide (LPS). Serum cytokine responses to intraperitoneal LPS injection were also evaluated. Splenocytes were isolated and their composition and functional responses were measured. The content of atractylenolide I and atractylenolide III, known anti-inflammatory ingredients, in AME was 0.0338 mg/g extract and 0.565 mg/g extract, respectively. AME increased the number of SRA(+)CD11b(+) cells in response to thioglycollate. Peritoneal macrophages isolated from the AME group showed no changes in inflammatory markers such as tumor necrosis factor- (TNF-) α, interleukin- (IL-) 6, inducible nitric oxide synthase, and cyclooxygenase-2 but exhibited a decrease in CD86 expression. Interestingly, AME decreased the serum levels of TNF- α and IL-6 upon intraperitoneal injection of LPS. Regarding the adaptive immune system, AME increased the CD4(+) T cell population and major histocompatibility complex class II molecule expression in the spleen, and cultured splenocytes from the AME group showed increased production of IL-4 concurrent with decreased interferon- γ production during T cell activation. AME promoted the replenishment of peritoneal macrophages during the inflammatory response but its anti-inflammatory activity did not appear to be mediated by the modulation of macrophage activity. AME also altered the immune status of CD4 T cells, promoting the Th2 response.